PATH COEFFICIENT ANALYSIS G39ÃCIHERANG AND MENTIK WANGIÃG39 RICE IN F4 GENERATION - D.H., Totok Agung; Azis, Fuad Nur; Hidayat, Ponendi; Susanti, Dyah; Riyanto, Agus; Zheng, Shao Hui (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
Current research was conducted with the objectives to identify the utmost traits that may be beneficial for the higher productivity of the grains on high protein content genotypes lines by path coefficient. Path coefficient can define coefficient correlation directly and indirectly to gain information about nature relationship between yield component and protein content to grain yield. Research material consisted of 61 selected plants from G39ÃCiherang and 66 selected plants from Mentik WangiÃG39 at F4 generation. Plants were planted in Banyumas in May 2011. Number of panicles per plant, panicle length, 1000 g of grain weight, percentage of filled grain per panicle, protein content, and grain yield were correlated by using Pearson correlation and were followed by path coefficient. Number of panicles per plant, panicle length, 1000 g of grain weight, percentage filled grain per panicle, and protein content were used as dependent variable, while grain yield was used as independent variable. The result showed that protein content in both populations was not correlated with all yield components. The numbers of panicles, followed by panicle length, had highest positive direct effect to yield. The number of panicle was a positive mediator variable to yield from another variable.Keywords: correlation, direct effect, indirect effect, mediator variable, path analysis